PENGARUH PENGALOKASIAN BANTUAN LANGSUNG MASYARAKAT (BLM) PNPM MANDIRI PERDESAAN DALAM RANGKA MENINGKATKAN KESEJAHTERAAN MASYARAKAT (Studi Kasus Pada Kecamatan Kendawangan, Kabupaten Ketapang) - B01111099, Gogo (Jurnal Pembangunan dan Pemerataan, 2015)
This study is entitled "Effects of Direct Aid Allocation Society (BLM) PNPM Mandiri to Improve Public Welfare" (THE CASE STUDY ON KECAMATAN KENDAWANGAN, KABUPATEN KETAPANG). This research is focusing on the issue of how the mechanism of society empowerment in efforts to reuce poverty through National Program for Society Empowerment in the village and how the implementation of poverty reduction through the National Implementationl of Society Empowerment Program (PNPM) in the village in Kecamatan Kendawangan. This research was the research in the field that in Kecamatan Kendawangan, the characteristic of this research is descriptive analysis that aim to describe and explain systematicly, actual and accurate information on the mechanisms and implementation of PNPM Mandiri in the village that in implementation program in Kecamatan Kendawangan. In collecting data, the researcher used secondary data, that sourced by West Kalimantan Province of Government Society Empowerment Board and Village Government, and Kecamatan Kendawangan and the others that involved in this research that has got from onservation in the field and also through interview with the others. Based on research in field we can conclude that the mechanisms and the implementation from the program of rural PNPM in Kecamatan Kendawangan that availble with the Technical Instructions Operations (PTO) that applicable in according with the plan, and able to improve the society welfare, especially on society empowerment that will increase revenue. Keywords: Mechanism, Implementation, Rural PNPM, Community Empowerment, Poverty and Welfare